Optimalisasi Upaya Preventif Melalui Skrining Kesehatan Gerak Dan Fungsi Dalam Aksi Nasional Fisioterapis - Lilik Sigit Wibisono; Purna Luberto; Fitratun Najizah; Syurrahmi Syurrahmi; Ni Kadek Krisna Dwi Patrisia; Mutiara Andriyani; Rafif Aydin Maheswara; Aisya Rahmah; Cintya Putri Anisah; Bernadiktus Reynaldo Nathanael; Radhita Ananta Putri (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
The Indonesian Physiotherapy Association, supports its member organizations to promote the profession in support of increased promotive and preventive efforts in their respective environments. Action Call June 10, 2023 is a special day, commemorated as the 55th anniversary of the Indonesian Physiotherapy Association, but also commemorated as Indonesian Physiotherapy Day, as a tribute to physiotherapists throughout the country. The synergy and collaboration that occurs due to the interaction of planning and executing activities internally in professional organizations according to their respective levels, is expected to be able to collaborate with policy makers, stakeholders and the community. Other elements of physiotherapy, such as elements of physiotherapy educational institutions, members of the Indonesian Physiotherapy Student Association and other elements are expected to actively and proactively participate to be involved together in supporting the Healthy Indonesia Program, and increasing the role of promotive and preventive efforts in order to improve the health status of the Indonesian people. STIKES Kesdam IV / Diponegoro is a health college that has a high dedication to the health of the community The program to improve the degree of public health, thus providing community service grant support through an external funding scheme from Kesdam IV/Diponegoro in the National Action of Physiotherapy in collaboration with the Semarang City Branch of IFI. Activities that will be supported are spread across 3 locations in the Semarang City area, namely RSUD Dr. Adhyatma MPH Tugurejo, STIKES Telogorejo, and the Puskesmas Now Gunung Pati Semarang. The series of activities were carried out from July 1, 2023 to August 31, 2023, with the implementation of balance scrinning with the Fukuda Test, Flat Foot scrinning, heart risk counseling, counseling and practice of pregnant gymnastics, postpartum gymnastics, baby gymnastics, child growth stimulation exercises, and prevention of work accidents with work biomechanics.